Primary transitional cell carcinoma of the fallopian tube - Sarmiento-Piña, Maira (2024)
Primary fallopian tube carcinoma is rare among primary malignant neoplasms ofthe genital tract. It accounts for approximately 1% of all malignant neoplasms ofthe female reproductive tract and is most common in menopausal women. A veryrare histologic variant that may involve the fallopian tube is primary transitionalcell carcinoma. It resembles epithelial ovarian cancer histologically and clinically.However, patients often have non-specific symptoms. Preoperative diagnosis isdifficult due to the lack of specific diagnostic elements and the fact that it is rarelyconsidered preoperatively. Diagnosis is usually based on histopathologic findings.In comparison to typical fallopian tube adenocarcinoma, this carcinoma is probablynot as aggressive, has a better response to chemotherapy and a good prognosiscompared to epithelial ovarian carcinoma. It is important to consider primary tumorsof the fallopian tube in the differential diagnosis of pelvic tumors. A case of primarytransitional cell carcinoma of the fallopian tube is presented.